2006
DOI: 10.1007/s10582-006-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Photon-added coherent states for the Morse oscillator

Abstract: In the paper we have constructed and investigated some properties of the Perelomov's "generalized coherent states" and photon-added coherent states for the Morse onedimensional Hamiltonian (MO-PACSs), using the SU(2) group generators. We have found the integration measure in the resolution of unity and we have calculated some expectation values in the MO-PACSs representation. Using these states, the diagonal P-representation of the density operator is constructed as a new result for Morse potential. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…We have also constructed and examined the properties of CSs for different oscillators: Morse oscillator (MO) [8][9][10] and pseudoharmonic oscillator (PHO) [11][12][13].…”
Section: Different Kinds Of Cssmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also constructed and examined the properties of CSs for different oscillators: Morse oscillator (MO) [8][9][10] and pseudoharmonic oscillator (PHO) [11][12][13].…”
Section: Different Kinds Of Cssmentioning
confidence: 99%
“…Circumvalaţiunii No. [8][9][10][11][12]300012 Timişoara, Romania points of view which evinced some facts that we are not able to realize: (a) we cannot perform a quantum measurement without perturbing the state of the measured system; (b) we cannot determine the particle position and momentum simultaneously and with any precision; (c) we cannot perform a simultaneously measurement of polarization of the photon in a vertical and diagonal basis; (d) we cannot represent the image (or "photography") of individual quantum processes; (e) we cannot be able to reproduce an unknown quantum state.…”
Section: Introductionmentioning
confidence: 99%
“…Morse oscillator has been well utilized in modeling anharmonic molecular vibrations for which the reason it will be used herein as the system of interest for probing anharmonic nuclear dynamics. Different groups have expended efforts on developing anharmonic ladder operators for the purpose of constructing of Morse oscillator coherent states, [9][10][11][12][13][14][15] but not much on their utility and the corresponding operations of its coherent states in dynamics. For example, Popov and coworkers, and others, have reported important work on Morse oscillator coherent states, however their work was missing utility and operational properties of Morse coherent states.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Popov and coworkers, and others, have reported important work on Morse oscillator coherent states, however their work was missing utility and operational properties of Morse coherent states. [9][10][11] The motivation for our work is the recent article by Popov et al 15 where their results were reported in terms of sums and exponential derivatives. It turns out that employing partial differential equations approach can help eliminate the sums and derivatives and recast the results in a closed form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation